2016
DOI: 10.1177/2168479015625712
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Nurse Services in Clinical Trials: Usage and Industry Perceptions

Abstract: Building effective partnerships with 1 to 2 vendors is considered a key factor for long-term success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Where appropriate, trial sites could increase use of virtual procedures for safety monitoring and remote outcome assessments. Along with remote procedures, virtual or hybrid clinical trials could use in‐home nursing care to administer therapy, perform key lab tests and physical exams, and ensure the integrity of data collected remotely 67,68 . The use of mobile nursing has increased over the last two decades, providing a participant‐centric alternative to on‐site visits, and—in conjunction with virtual approaches—has the potential to offset the cost associated with trial delays due to slow enrollment and high dropout rates 67,68 .…”
Section: Recommendations For Accelerating Clinical Trials For Admentioning
confidence: 99%
See 2 more Smart Citations
“…Where appropriate, trial sites could increase use of virtual procedures for safety monitoring and remote outcome assessments. Along with remote procedures, virtual or hybrid clinical trials could use in‐home nursing care to administer therapy, perform key lab tests and physical exams, and ensure the integrity of data collected remotely 67,68 . The use of mobile nursing has increased over the last two decades, providing a participant‐centric alternative to on‐site visits, and—in conjunction with virtual approaches—has the potential to offset the cost associated with trial delays due to slow enrollment and high dropout rates 67,68 .…”
Section: Recommendations For Accelerating Clinical Trials For Admentioning
confidence: 99%
“…Along with remote procedures, virtual or hybrid clinical trials could use in-home nursing care to administer therapy, perform key lab tests and physical exams, and ensure the integrity of data collected remotely. 67,68 The use of mobile nursing has increased over the last two decades, providing a participant-centric alternative to on-site visits, and-in conjunction with virtual approaches-has the potential to offset the cost associated with trial delays due to slow enrollment and high dropout rates. 67,68 Further, virtual trials provide opportunities to recruit and retain participants in remote areas, and reach underrepresented populations.…”
Section: Virtual Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the proposed trial, mothers suggested providing home visits instead of staying overnight at the research site. Bringing the conduct of clinical trial assessments to participants is a definite way to improve patient recruitment and retention [38]. A recent breastfeeding study successfully used home visits to improve the recruitment and retention of lactating women [39].…”
Section: Discussionmentioning
confidence: 99%
“…Mobile nursing services in clinical trials have been broadening their reach, especially in North America and Western Europe. 6 eConsent manages patient consent using technology, but has not had much utilization. 7 Other uses of patient-centric initiatives can be seen in crowdsourcing protocols, defined as gathering input from patients, physicians, and other stakeholders via the World Wide Web, especially within oncology clinical trials.…”
Section: Introductionmentioning
confidence: 99%